Safety of intra‐arterial treatment in acute ischaemic stroke patients on oral anticoagulants. A cohort study and systematic review. (29th May 2015) - Rozeman, A. D.; Wermer, M. J. H.; Lycklama à Nijeholt, G. J.; Dippel, D. W. J.; Schonewille, W. J.; Boiten, J.; Algra, A.; ,
Abstract : Background and purpose: An elevated international normalized ratio (INR) of >1.7 is a contraindication for the use of intravenous thrombolytics in acute ischaemic stroke. Local intra‐arterial therapy (IAT) is considered a safe alternative. The safety and outcome of IAT were investigated in patients with acute ischaemic stroke using oral anticoagulants (OACs). Methods: Data were obtained from a large national Dutch database on IAT in acute stroke patients. Patients were categorized according to the INR: >1.7 and ≤1.7. Primary outcome was symptomatic intracerebral hemorrhage (sICH), defined as deterioration in the National Institutes of Health Stroke Scale score of ≥4 and ICH on brain imaging. Secondary outcomes were clinical outcome at discharge and 3 months. Occurrence of outcomes was compared with risk ratios and corresponding 95% confidence intervals. Further, a systematic review and meta‐analysis on sICH risk in acute stroke patients on OACs treated with IAT was performed. Results: Four hundred and fifty‐six patients were included. Eighteen patients had an INR > 1.7 with a median INR of 2.4 (range 1.8–4.1). One patient (6%) in the INR > 1.7 group developed a sICH compared with 53 patients (12%) in the INR ≤ 1.7 group (risk ratio 0.49, 95% confidence interval 0.07–3.13). Clinical outcomes did not differ between the two groups. Our meta‐analysis showed a first week sICH risk of 8.1% (95% confidence interval 3.9%–17.1%) in stroke patients with elevated INR treated with IAT. Conclusion: The use of OACs, leading to an INR > 1.7, did not seem to increase the risk of an sICH in patients with an acute stroke treated with IAT. Abstract : Clickhere to view the accompanying paper in this issue.